Barriers and facilitators for community pharmacists' participation in pharmacy practice research: a survey. (19th February 2019) - Kuipers, Esther; Wensing, Michel; De Smet, Peter A.G.M.; Teichert, Martina
Abstract: Objectives: The aim of this study was to explore pharmacists' barriers and facilitators regarding participation in pharmacy practice research. Methods: We conducted an online cross‐sectional survey in 1974 community pharmacies in the Netherlands. Key findings: A total of 252 pharmacists completed the questionnaire. The majority agreed that participation in research should be part of daily practice. Efficient time investment and a clear benefit for general professional knowledge, patient care and pharmacy organisation were the most important facilitating factors. Conclusions: To encourage pharmacists' participation, researchers should offer clear instructions, possibilities for flexible time management, simple patient inclusion, task delegation and no additional contacts with healthcare professionals due to the research.